USE OF KERNEL DENSITY ESTIMATES IN THE RESEARCH OF FORMATIVE PERIOD CERAMICS FROM CHAVIN DE HUANTAR - Mesía Montenegro, Christian (2012)
In this paper I analyze a sub set of 3020 diagnostic ceramic sherds recovered in five spatial units identified in Chavín de Huántar, Peru, in order to find patterns of association between the categories of diameter and thickness per type of ceramic vessel and to identify possible differences of those patterning’s among spatial units. I have used Kernel Density Estimates (KDE) for the purpose of identify modalities in diameters and thickness per type in each spatial unit.